STRATEGI PENGEMBANGAN WISATA RELIGI DALAM MENINGKATKAN KUNJUNGAN WISATA DI KOTA SEMARANG - Muhammad Sandy Yudha Putra Pratama; Tri Yuniningsih (Journal of Management and Public Policy, 2026)
The development of religious tourism in Semarang City represents a strategic issue in regional tourism development due to the increasing demand for tourism experiences that emphasize spiritual, cultural, and educational values. However, the sector has not been optimally managed, as reflected in governance weaknesses, limited innovation in tourism programs, and the inadequate integration of digital promotion and public service quality. This study aims to formulate effective development strategies for religious tourism in order to increase tourist visits in Semarang City. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation. Data analysis was conducted using SWOT analysis to identify internal and external factors influencing the development of religious tourism. The findings indicate that religious tourism in Semarang City possesses strong potential in terms of attractions, accessibility, and government support, yet continues to face challenges such as weak coordination among destination managers, low professional capacity of human resources, and inconsistent service quality, particularly regarding cleanliness, safety, and visitor comfort. Based on the SWOT analysis, three main strategies were formulated: strengthening integrated digital promotion, enhancing the capacity and professionalism of tourism managers, and developing culturally and educationally oriented tourism programs. This study concludes that the implementation of integrated and sustainable strategies plays a crucial role in improving the competitiveness of religious tourism and increasing tourist visits in Semarang City.